Hubungan Paparan Pestisida Dengan Kejadian Goiter Pada Petani Hortikultura Di Kecamatan Ngablak Kabupaten Magelang - Sungkawa, Hendra Budi; Setiani, Onny; Suhartono, Suhartono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2007)
ABSTRACT Background: Pesticides are toxic material or a substance or mixture of substances used to kill a pest or intended for preventing, destroying, repelling or mitigating any pest.[2] A pesticide may be a chemical substance, biological agent (such as a virus or bacterium), antimicrobial, disinfectant or device used against any pest. Pests in agriculture include insects, plant pathogens, weeds, molluscs, birds, mammals, fish, nematodes (roundworms. Although there are benefits to the use of pesticides, there are also drawbacks, such as potential toxicity to humans and environment. Usage pesticide which do not well managed may generate negative impact. Chronic poisoning of pesticides may produce adverse effect on health, including, cancer, genetic mutation, thyroid diasease, reproductive disorders and neurodegenerative disases. Preliminary researh showed that farmer in district of Ngablak 98 % have experience of pesticide exposure. Result of study indicate that 16,5 % farmer of horticulture that have pesticide exposure district of Ngablak have a disorder of thyroid and manifest as goiter. This research objective was to find out the relation between pesticides exposure and the incidence of goitre on farmer exposed to pesticides. Method: this research used a case control design with 68 case and 68 control. The variable of the research include age, education, work duration, time of activity per day, pesticide type, pesticide dose, spraying frequency, time of spraying, farmer position to wind direction while spraying and using of personal protective equipment. Result: Research result indicated that variables that related to the incidence of endemic goitre were age (OR = 3,83; CI 95%= 1,88 – 7,81), work duration (OR = 12, 79; CI 95% = 2,85 – 57,53), time of activity per day (OR = 2,47; CI 95% = 1,16 – 5,23), pesticide type (OR = 5,86; CI 95% = 2,73 – 12,56), pesticide dose (OR = 2,96; CI 95% = 1,37 – 6,42), spraying frequency (OR = 4,69; CI 95% = 2,28 – 9,69), farmer position to wind direction while spraying (OR = 3,07; CI 95% = 1,39 – 6,77), using of personal protective equipment (OR = 3,18; CI 95% = 1,57 – 6,41). Conclusion: Farmer’s risk factor to the incidence of endemic goitre is working time time of activity per day, pesticide type, spraying frequency, farmer position to wind direction while spraying and the use of personal protective equipmetn, in its contribute 33,78%. Probability to the incidence of goitre on farmer exposed to pesticides. Keyword : pesticide exposure, pesticides type, work duration, incidence of goitre, farmer